2020
DOI: 10.3389/fonc.2020.01168
|View full text |Cite
|
Sign up to set email alerts
|

WNT2-Mediated FZD2 Stabilization Regulates Esophageal Cancer Metastasis via STAT3 Signaling

Abstract: Esophageal cancer micro environment factor WNT2 was critical in cancer metastasis. However, very little is known about WNT2 receptors and their role in the malignant progression of ESCC. The clinical significance and underlying molecular mechanisms of FZD2, one of the receptors of WNT2, was further investigated in ESCC. We found that FZD2 expression was positively correlated with WNT2 levels in clinical ESCC specimens through database analysis. Upregulated FZD2 expression was detected in 69% (69/100) of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…As the receptors of the Wnt signaling pathway, FZDs activate downstream signaling by binding to Wnt ligands, further regulating cell proliferation, differentiation, migration, tissue polarity, and tumor development. FZDs have been found to be specifically expressed on the cell plasma membrane, and FZD2 is one of the most important receptors in the noncanonical Wnt pathway; it is highly expressed in many cancers and is a marker of poor prognosis [9,19,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the receptors of the Wnt signaling pathway, FZDs activate downstream signaling by binding to Wnt ligands, further regulating cell proliferation, differentiation, migration, tissue polarity, and tumor development. FZDs have been found to be specifically expressed on the cell plasma membrane, and FZD2 is one of the most important receptors in the noncanonical Wnt pathway; it is highly expressed in many cancers and is a marker of poor prognosis [9,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the important receptors of the Wnt signaling pathway and is mainly involved in nonclassical pathway signal transduction [5]. It is highly expressed in a variety of malignant tumors and participates in the regulation of various tumor behaviors [6][7][8][9]. Its expression level is closely related to patient prognosis, and therefore, it is expected to become a new prognostic indicator and therapeutic target for a variety of cancers [10,11].…”
mentioning
confidence: 99%
“…FZD2 encodes a transmembrane protein with seven transmembrane domains and an extracellular cysteine-rich domain [40,41]. It can strongly bind to Wnt proteins, which subsequently activates the expression of downstream genes by the Wnt signaling pathway [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…FZD2 encodes a transmembrane protein with seven transmembrane domains and an extracellular cysteine-rich domain [40,41]. It can strongly bind to Wnt proteins, which subsequently activates the expression of downstream genes by the Wnt signaling pathway [40,41]. A study performing a comprehensive analysis of FZD2 in 33 cancer types indicated that FZD2 was associated with high oncogenicity [42].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been observed that increasing miR-135b expression in chemoresistant NSCLC cell lines decreases Fzd1 expression and increases drug sensitivity ( Su et al, 2016 ). Fzd2, commonly expressed in fetal lung, brain, and kidney, as well as adult cardiac tissue, has been identified as an upregulated tumorigenic receptor in multiple cancers from primary tumors to metastatic tissues ( Sagara et al, 1998 ; Zhang et al, 2015 ; Fu et al, 2020 ). MicroRNAs that inhibit Fzd2 expression and signaling lead to inhibition of tumorigenesis.…”
Section: Micrornamentioning
confidence: 99%